Leadership in Action: Building Talent: Developing Effective Leaders is as Crucial as Ever - Berke, David; Kossler, Michael; Wakefield, Michael (Center for Creative Leadership, 2009)
Even in the midst of economic upheaval, some organizations recognize that making sure they have the right leadership talent in place will help them not only survive but thrive when the economy eventually rebounds. Developing leadership talent requires a systematic approach that begins with the organization's strategic goals and takes into account developmental needs at both the organizational and individual levels.
Keywords: Leadership